Transition to Circular Economy and Management of Public Services of General Economic Interest - Sandra Antoniazzi (Central European Public Administration Review)
Purpose: The aim of this paper is to clarify the topic of the transition to circular economy, an expression of the European “Green New Deal”, which has several application consequences for the SGEI sector. Approach: The approach consists of examining the European policy framework, the most relevant consequences of the transposition of the 2018 waste directives for the domestic system, the new measures for local authorities and users, and the new “purpose” of the utilities industries based on sharing and environmentally friendly solutions. Findings: The study highlights the need for several practical adjustments in the implementation of circular economy: the necessary technological innovation requirements for industrial production, reforms of the national legal framework, and an inevitable wider cultural evolution. Publications concerning the transition to circular economy in relation to public services of the general economic interest sector are not numerous in law literature. Most of the existing documents and communications are provided by the European Commission and the analyses are based mainly on the guidelines of the new green policy and the specific EU legal framework. Academic contribution to the field and originality/significance/value: The paper adds to existing research focusing mainly on legal studies of the wider consequences for national utility policy and companies’ business plans, the role of local public authorities having direct powers that need reforms, and the position of consumers.